Preparation of pre-service teachers for English first additional language teaching: A literature review approach - Nomfundo Philile Nkala (International Journal of Studies in Inclusive Education)
Pre-service teachers in English First Additional Language (FAL) preparation programmes are designed to skill with knowledge so they become competent teachers. This study underpinned the historical development of English language teaching in South Africa and preparing pre-service teachers for English FAL teaching in schools. It highlighted the role of higher education institutions in preparing pre-service teachers for English language teaching and the importance of teacher education curriculum and pedagogy. It discussed the teaching and learning of the English language and presented some approaches used for English language development in teacher education. It finally recommends extending the practicum period for greater exposure to natural classroom environments and ensuring that the qualification requirements are uniform so that teachers are adequately prepared to teach in different school contexts. Pre-service teachers must be exposed to speaking and presenting so they do not get overwhelmed in crowded classrooms.